Peningkatan pembelajaran IPS dengan menggunakan model kooperatif tipe Student Team Achievement Division (STAD) di kelas V SDN 36 Rangeh Kecamatan Lengayang Kabupaten Pesisir Selatan - Sefrinel Dewita (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
This research started from reality at school that in learning process learners just sit, silence, listen, and record material submitted by a teacher. This is because teachers are less able to develop learning models that can enable learners optimally in the learning process. As a result, learners are often not excited and feel saturated in learning, so that the learning outcomes are low. To improve the activity and learning outcomes of learners in IPS learning done PTK by using the STAD type cooperative model. STAD type cooperative model is a learning model that puts learners in groups of five or six students. This research was conducted in class V SDN 36 Rangeh Kecamatan Lengayang, with the number of students 27 people. From the results of research conducted it can be concluded that by using STAD type cooperative learning model can improve the activity and learning outcomes of learners in learning social studies in class V SDN 36 Rangeh Kecamatan Lengayang.